Preschool teachers’ knowledge, beliefs, and self-efficacy concerning autism: a parallel mixed-methods study of an intervention to improve autism identification - Taresh, Sahar Mohammed; Morett, Laura M; Zaid, Sumaia Mohammed; Roslan, Samsilah; Taresh Taleb, Mohammed; Song, Pu; Ahmad, Nor Aniza; Noman, Sarah (SAGE Publications Ltd., 2024)
Preschool teachers can play a critical role in early detection of autism. Equipping preschool teachers with prerequisite knowledge and skills would allow them to identify children with probable autism and referral to diagnostic services. This study aimed to investigate the impact of an educational module (EMiASD) that prepared preschool teachers to identify autism symptoms. The sample included 144 preschool teachers, of which 120 were stratified and randomly assigned to an intervention arm receiving training in EMiASD (n = 60) or a comparison arm receiving standard training (n = 60) using a parallel mixed-methods design. Responses to open-ended questions about video case studies revealed improvement in the identification of autism symptoms in preschool teachers in the intervention arm, in contrast to preschool teachers in the comparison arm. Moreover, significant changes in knowledge, belief, and self-efficacy about autism favoured EMiASD. Overall, these results demonstrate the influence of EMiASD in the Yemeni cultural context. Lay Abstract: Preschool teachers can play a critical role in early detection of autism. Equipping preschool teachers with prerequisite knowledge and skills would allow them to identify children with probable autism and referral to diagnostic services. This study aimed to investigate the impact of an educational module (EMiASD) that prepared preschool teachers to identify autism symptoms. The sample included 144 preschool teachers, of which 120 were stratified and randomly assigned to an intervention arm receiving training in EMiASD (n = 60) or a comparison arm receiving standard training (n = 60) using a parallel mixed-methods design. Responses to open-ended questions about video case studies revealed improvement in the identification of autism symptoms in preschool teachers in the intervention arm, in contrast to preschool teachers in the comparison arm. Moreover, significant changes in knowledge, belief, and self-efficacy about autism favoured EMiASD. Overall, these results demonstrate the influence of EMiASD in the Yemeni cultural context.